Metaphor on Tanggap Wacana Panyandra in Panggih Manten Ceremony of the Java Ethnic Group - Adelia Fitri Sabrina; Amrin Saragih (TRANSFORM : Journal of English Language Teaching and Learning, 2021)
This study was aimed at identifying the types of metaphors contained in Panyandra Panggih Manten Ceremony of Javanese ethnicity. And the meaning contained in the metaphor. This study was conducted by applying descriptive qualitative method. The source of data was taken from the documentary transcription from recording the wedding ceremony event. The results of this research showed that written text can be analyzed by using metaphor. From that findings of the analysis conducted, there are 20 metaphorical units in the Javanese traditional wedding ceremony Panyandra, and have fulfilled all the categories by Crystal, Beckson and Ganz theory. Placing the conceptual metaphor category as the highest percentage category of 60% (12 units), next is the mixed metaphor category with a percentage of 15% (3 units), then the poetic metaphor category with the lowest percentage result with 25% (5 units).